Program Skrining Keliling Tekanan Darah Sebagai Langkah Awal Deteksi Dini Hipertensi di Dusun Badengan, Desa Kluncing, Kecamatan Licin, Banyuwangi - Melati Octavia Febriana; Septa Indra Puspikawati; Diansanto Prayoga; Avila Abilia; Firrial Eksa; Uyun Loveni; Anggi Margareta; Putri Nur; Oktario Dinansa; Nafkha Nisa; Lailatu Rohmah; Imelda Damayanti; Muhamad Isa; Fertika Nanda (Abdimas Universal, 2024)
Hypertension is one of the most prevalent NCDs. The importance of controlling NCDs is due to the high incidence and mortality rates. NCD control is better with early prevention, especially in Kluncing Village, Licin District, Banyuwangi.. One of the early prevention is the existence of the Blood Pressure Mobile Screening Program as an Early Step for Early Detection of Hypertension in Badengan Hamlet, Kluncing Village, Licin District, Banyuwangi. The goal of this program is to focus on early detection of hypertension and enable earlier identification of cases. Early detection is crucial to prevent serious complications that can arise from hypertension, such as heart disease and stroke. In addition, by bringing screening services closer to the community, this program can improve the accessibility of health services. The method of implementation begins with program planning, problem identification, priority determination, causes of problems, alternative solutions, preparation of a proposed plan to plan implementation. This program is implemented through door to door screening using blood pressure and education about hypertension, as well as involving the Licin Health Center in handling people with hypertension. Based on the results of blood pressure measurements, 91 people (28%) had normal blood pressure, 153 people (46.5%) had prehypertension, 60 people (18%) had grade 1 hypertension, and 25 people (7.5%) had grade 2 hypertension. In its implementation, the performance indicator has reached the target of 52.55% or 329 community members who were screened for hypertension by measuring blood pressure. This shows that the hypertension screening program is running effectively and achieving its goal of detecting hypertension in the community.